PERSEPSI INDIVIDU TERHADAP PESAN VISUAL DAN VERBAL DALAM KAMPANYE KOSMETIK CRUELTY-FREE DI INSTAGRAM - Alissa Vernanda Irvanoputri; Putu Riana Artyanti Putri (UNIVERSITAS STEKOM, 2026)
This study aims to explore individual perceptions of visual and verbal messages within cruelty-free cosmetic campaigns on Instagram. Using a qualitative descriptive method, data were gathered through digital observations and in-depth interviews with followers of local cosmetic brands. The results indicate that the synergy between natural aesthetic visuals, such as earth-tone palettes and certification logos, with transparent verbal narratives significantly builds consumer trust. Individual interpretations are heavily influenced by digital literacy and personal moral values regarding animal welfare. A positive perception ultimately transforms passive followers into loyal brand advocates who are willing to pay premium prices for ethical products. These findings suggest that consistent, transparent communication is essential for brands to avoid greenwashing allegations and maintain long-term consumer loyalty in the digital era.